Variabilidade da fitomassa de frutos de abobrinha italiana e de tomate e o planejamento experimental - Carpes, Ricardo Howes (2008)
To verify the variability interference of the estimates of the values used to determinate the plot size with simulations of different numbers of plants per plot and groupings of crops, a five-experiment work was carried out. One in the winter/spring of 2004, other in the summer/autumn of 2005 for the zucchini and three experiments with tomato in the winter/spring of 2007, accomplished at Department of Phytotechny of UFSM, RS. In the experiments with zucchini, plastic tunnel was used, with drip irrigation, black mulching of PEDB, three lines with 24 plants per row, spacing among plants 0,8m and among lines 1,2m. For the tomato, the same plastic tunnels were used in two experiments and a plastic greenhouse in the third, that one with dimensions of 24m long and 10m wide in 8 cultivation rows. In the five experiments, each plant was considered as a basic unit (UB) of the plot size. The sequence of two, three and four plants in the crop line formed the plots of two, three and four UB of size (X). For each estimate in each experiment, analyses were accomplished considering only considered individual and combined harvests. For each one of the five experiments, the estimates of the average, of the variance, of the variation coefficient, of the index relative information and of the relative coefficient had been obtained. The Bartlett test was applied among the variances of the individual and combined harvests in each size of simulated plot and among the plot sizes in each individual and combined harvest to verify the homogeneity among the variances within each harvest in different plot sizes. For both cultures, there were some increases in the estimates of the average and in the variance of the fitomass of fruits with the increase of the size of the plot and/or the number of grouped harvests. For the zucchini, the variances, among the grouped harvests, were homogeneous, considering the grouping of three harvests, while for the tomato only in the groups of six harvests. The relative information index and the relative coefficient present more appropriate values, independently of each culture, considering the groups of harvests. The arrangement of two groups of combined harvests, joined with plots of three plants for Italian zucchini and of four plants for tomato, reduce the variability among plots.